Whistleblowing in India: evidence from accounting students and professionals. Issue 1 (28th January 2020) - Brody, Richard G.; Gupta, Gaurav; White, Todd
Abstract : Purpose: The purpose of this paper is to examine whistleblowing behavior in the accounting community (students and professionals) in an emerging economy – India. Design/methodology/approach: Using a case-based approach, data were collected from 263 accounting students and 268 accounting professionals in India. Findings: Using multivariate and univariate analyses of variance and logistic regressions, the authors provided evidence on how accounting students and professionals behave in a whistleblowing environment. Specifically, the authors found mixed results when comparing the behavior of accounting students and professionals in a whistleblowing scenario. All subjects reflected a more collectivist attitude, although professionals were more concerned about "fixing" the identified internal control problem (a "shared" problem). Both groups expressed a firm desire to collect more evidence against the likely fraudster. Practical implications: In this era of global offshoring of services including accounting, the current study makes significant contributions to the accounting ethics literature and the accounting profession by analyzing whistleblowing behavior from an Indian perspective – a highly underrepresented area in the accounting ethics literature. The study aims to guide companies and investors in the US and elsewhere that do business in India. Originality/value: While the accounting literature has plenty of research on whistleblowing in the Western world, there is a dearth of literature on whistleblowing in India. This paper is among the first to document whistleblowing behavior in India, a country that prides itself on its vast availability of English-speaking and technically sound accounting professionals.